The prophylaxis of venous thromboembolism in medical outpatients: results of a survey among italian general practitioners - Badinella Martini, Marco; Dentali, Francesco; Pizzini, Andrea; D'Ascenzo, Fabrizio; Fenoglio, Luigi; Pomero, Fulvio (Acta Biomedica Atenei Parmensis, 2020)
Background: Although the majority of venous thromboembolic events occurs in primary care, most of the studies concerning its prophylaxis investigate hospitalized patients. Therefore, in primary care, many clinical decisions have to be taken in the absence of great clinical evidence derived from studies performed directly on outpatients. The objective of our study is to evaluate the clinical approach of Italian General Practitioners to the prophylaxis of venous thromboembolism in medical outpatients. Methods: A web-based questionnaire was emailed to 766 Italian General Practitioners. In the questionnaire there were four exemplary clinical cases concerning hypothetical patients at venous thromboembolic risk. Results: Overall 232 questionnaires were returned. Approximately 40% of the participants reported to assess thrombotic and hemorrhagic risk with a risk assessment model but nevertheless only a narrow minority had recourse to a suitable and validated score for this purpose. In the chronically bedridden patient about half of the participants administered a heparin or an antiplatelet drug for long time. In acute outpatients at high venous thromboembolic risk there was a considerable underuse of heparin prophylaxis and graduated compression stockings were often considered as a first prophylactic option. Prolonged heparin prophylaxis in the post-acute setting was also the practice for half of the participants. Conclusions: Italian General Practitioners approach these “grey” areas of uncertainty in a significantly heterogeneous way and sometimes in sharp contrast to the recent evidence.  The present findings stress the need for further targeted educational programs and new high quality studies to further deep this clinical context.